Pengaruh Penambahan Abu Serabut Kelapa Terhadap Permeabilitas Tanah Lempung - Evidelis Kala'lembang; Irwan Lie Keng Wong; Benyamin Tanan (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
The purpose of this study is to determine the physical properties of the soil and to determine the impact that occurs as a result of the addition of coconut fiber ash to the permeability coefficient of clay soils. The test was carried out by the falling head method. Soil samples were obtained from Rantebua village, Rantebua district, North Toraja regency and coconut fibers used as added material obtained from community waste in Makassar City with a percentage of added materials of 0%,15%,20% and 25%. This study used a series of studies on the physical properties of the soil then to obtain the coefficient of soil permeability, it was arranged to the composition of the alloy against the soil permeability test. Sample testing was carried out at the Soil Mechanics Laboratory of UKI Paulus Makassar. From the results of the research conducted, it has shown that the soil that has been tested meets the characteristics, namely as clay soil. There is a decrease in the permeability value caused by the addition of coconut fiber ash, namely the higher the percentage of coconut fiber ash, the smaller the permeability tilapia up to the addition of 25%.